Forecasting tourism demand for Lisbon’s region through a data mining approach - Ricardo, Hugo (2022)
Ricardo, H., Ivo, G., & Costa, A. C. (2018). Forecasting tourism demand for Lisbon’s region through a data mining approach. In M. B. Nunes, P. Isaías, & P. Powell (Eds.), Proceedings of the 11th IADIS International Conference Information Systems 2018 (pp. 58-66). IADIS Press. ISBN: 978-989-8533-74-6